Pengaruh Belanja Modal dan Belanja Barang dan Jasa Terhadap Tingkat Pengangguran dan Kemiskinan di Provinsi Sumatera Utara - Hanisah (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2024)
This study analyzes the influence of capital expenditures and current expenditures on unemployment and poverty levels in 33 regencies/cities of North Sumatra Province during the 2010-2020 period using panel data. The estimation results show that capital expenditures have a positive and significant effect on poverty levels, while current expenditures have a negative and significant effect on poverty levels. Meanwhile, capital expenditures do not have a significant effect on unemployment rates, but current expenditures have a negative and significant effect on unemployment rates. These findings provide policy implications for local governments to optimize the allocation of current expenditures in reducing poverty and unemployment, as well as to review strategies and policies related to capital expenditures to have a positive impact in the long term.